2020
DOI: 10.4081/ejtm.2020.9236
|View full text |Cite
|
Sign up to set email alerts
|

Balance and muscle strength tests in patients with osteoporotic vertebral fractures to develop tailored rehabilitation programs

Abstract: Authors perform a cross-sectional study of functional abilities of the patients with osteoporotic VF. Trunk muscle isometric strength and balance impairments were estimated. The development of osteoporotic VFs is associated with a significant decrease in strength of all the body muscles, especially the deep spinal stabilization system (TE, TF), where the VFs contribute to inappropriate distribution of back muscle strength with TE:TF ration of 1:1 instead of 3:2, observed both normally and in patients with unco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 23 publications
0
5
0
4
Order By: Relevance
“…Pain control could promote adherence to rehabilitation treatment with putative improvement of muscle impairments that are commonly observed in patients with severe osteoporosis, including those with multiple vertebral fractures [ 33 , 34 ]. In a real practice prospective study, including osteoporotic women with vertebral fractures (50% of participants had at least three fractures) and chronic back pain, 1-year denosumab administration resulted to be effective in reducing back pain related disability and QoL after 6 months of treatment [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pain control could promote adherence to rehabilitation treatment with putative improvement of muscle impairments that are commonly observed in patients with severe osteoporosis, including those with multiple vertebral fractures [ 33 , 34 ]. In a real practice prospective study, including osteoporotic women with vertebral fractures (50% of participants had at least three fractures) and chronic back pain, 1-year denosumab administration resulted to be effective in reducing back pain related disability and QoL after 6 months of treatment [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon emphasizes the validity of training on special equipment aimed at training the deep stabilization system of the spine, and can also be considered as a point of application of rehabilitation measures. 27 General weakening of the muscle strength and muscular corset, in particular, degenerative changes in bone tissue and joints, deformities of skeleton after fractures and formation of hyperkyphosis, impaired proprioceptive sensitivity and vestibular apparatus. All this leads to impaired coordination of motor abilities in patients with osteoporotic VF, 28,29 which is also confirmed by our data.…”
Section: Discussionmentioning
confidence: 99%
“…A tailored rehabilitation program based on balance and muscle strength tests has recently been proposed as an effective treatment option for basic motor function improvement and disability reduction [ 29 , 30 ]. A retrospective observational study found that compliance with a home exercise program was 62.86%, with several causes of non-compliance, including the absence of supervision by health personnel and a lack of motivation [ 31 ].…”
Section: Conservative Treatmentmentioning
confidence: 99%